Right heart thrombosis in patients with pulmonary embolism: a case series - M. A. Teterina; D. A. Ubaydullaeva; N. A. Farzalieva; A. R. Nazyrova; M. G. Jayasinghe Havpage; A. A. Lapshin; I. Meray; Zh. D. Kobalava (Российский кардиологический журнал, 2024)
Currently, recommendations have been developed for the treatment of patients with pulmonary embolism. However, the optimal management tactics for such patients in the presence of right heart thrombosis remains a matter of argument. Timely detection of right heart thrombosis can influence the choice of treatment tactics, which will help reduce the risk of adverse outcomes. The article presents three clinical cases with different clinical course options and management strategies that take into account risk factors and prognosis.